Zastosowanie analizy kosztów i korzyści do oceny inwestycji w krajach rozwijających się - Janc, Alfred (Wydział Prawa i Administracji UAM, 1986)
The subject of the article is the Western elaborated method of investment estimation known as cost-benefit analysis, discussed in the context of investment processes and problems of estimating investment ventures in the developing countries. Development of methodological concepts of cost and benefit analysis is presented as well as relations of investment estimation to planning the socioeconomic development. Particular attention is paid on the methods elaborated within the framework of such international organizations as OECD, UNIDO, IDCAS and the World Bank. The author focuses on two basic elements of the cost-benefit analysis, i.e. searching for a numeraire- a unit of account and settlement valuation of expenditures and results. The author discusses both various methods of arriving at settlement prices for the needs of estimation development investments and the meaning of the so-called national parameters i.e. dual valuations having the same values in analysis of all examined and evaluated undertakings in a given state in a given period. The article indicates at the wide interest paid to the concept of cost-benefit analysis recently in the developing countries. It is emphasised that a large body of literature is devoted to the theory of cost and benefit analysis as well as numerous performed and described practical applications of the formulated methods.
Application of cost and benefit analysis to estimation of investments in the developing countries